Analisis Yuridis Tindak Pidana Penggelapan Berdasarkan Pasal 372 Kitab Undang-Undang Hukum Pidana: Studi Kasus 2 Perkara No. : 16/Pid.B/2022/PN.Pti - Khamim; Nuno Guilhermino Pacheco Magno (Jurnal Hukum dan Demokrasi (JHD), 2025)
The main condition for the existence of a criminal act is the existence of rules that prohibit and are subject to criminal sanctions for anyone who violates it, one of the rules contained in the Kitab Undang-Undang Hukum Pidana (KUHP). Criminal liability can occur if there is an error caused by intent, negligence and the absence of excuses. In certain offenses, criminal liability can occur before the existence of criminal acts and the actions committed are the realization of part of criminal responsibility. An example of a problem is that there is an initial intention that is not categorized as a crime, but it can become a crime if the intention changes, such as when we borrow or rent goods from other people for a few days, but on the last day the borrower changes his intention to hold the item. So it can be categorized as embezzlement as in Case No. : 16/Pid.B/2022/PN.Pti.